The roles of shape and texture in the recognition of familiar faces. (May 2022) - Rogers, Daniel; Baseler, Heidi; Young, Andrew W.; Jenkins, Rob; Andrews, Timothy J.
Abstract: The surface texture of the face is proposed to be the dominant cue in face recognition. In this study, we investigated the role of shape information in face recognition. We compared the roles of shape and surface texture in the recognition of face identity using familiar and unfamiliar hybrid faces in which the average shape from one facial identity was combined with the average texture of a different identity. In the first experiment (n = 53), participants had to match the name of a familiar person to one of eight hybrid face images. In texture trials, all images had the correct shape, but only one image had the correct texture. In shape trials, all images had the correct texture, but only one image had the correct shape. Importantly, neither task could be performed by perceptual matching. Although performance was lower for the shape trials (81%) compared to texture trials (99%), both were significantly above chance (12.5%). In the second experiment (n = 110), participants had to name hybrid faces. There were two potentially correct answers for each face image: one based on the texture and one based on the shape. Participants reported the correct name based on the texture on 61% of trials and the correct name based on the shape on 12% of trials. In the third experiment (n = 19), fMR-adaptation was used to measure the neural sensitivity to changes in the shape or texture. The core face-selective regions showed a similar sensitivity to shape and texture. These findings confirm that texture is the dominant cue for face recognition, but also show that shape plays an important role in the recognition and neural response to familiar faces.